A Review on Leakage Power Reduction Techniques at 45nm Technology. (2015) - Kumar, N. Praveen; Charles, B. Stephen; Sumalatha, V.
Abstract: There is a growing need to analyze and optimize the stand-by component of power in digital circuits designed for portable and battery-powered applications like laptops and mobiles. Since these devices remain in stand-by mode significantly longer than in active mode, their stand-by current, and not their active switching current, determines their battery life. Hence, stringent specifications are being placed on the stand-by current drawn by such devices especially at nanometer regime. As the power supply voltage is reduced, the threshold voltage of transistors is scaled down to maintain a constant switching speed. Since reducing the threshold voltage increases the leakage of a device exponentially, leakage current has become a dominant factor in the design of VLSI circuits. In this paper we presented various techniques to reduce the standby power at 45 nm technology.